MEK inhibition induced downregulation of MRP1 and MRP3 expression in experimental hepatocellular carcinoma - Lin Shibo; Hoffmann Katrin; Xiao Zhi; Jin Nan; Galli Uwe; Mohr Elvira; Büchler Markus W; Schemmer Peter (Cancer Cell International, 2013)
Abstract Background Hepatocellular carcinoma (HCC) exhibits strong intrinsic and acquired drug resistance which is the main obstacle to chemotherapy. Overexpression of ATP binding cassette (ABC) proteins correlates with activation of mitogen activated protein kinase (MAPK) pathway in HCC. Here, we systematically investigated the inhibition of MAPK pathway and its role in regulating HCC cell growth as well as ABC proteins MRP1 and MRP3 expression. Methods The Raf1 kinase inhibitor (GW5074) and different MEK inhibitors (U0126 and AZD6244) were used to treat HCC cells to identify their effects on HCC cell growth and ABC proteins expression in vitro. Cell viability tests were performed after the treatment of MAPK pathway inhibitors and in combination with gemcitabine or doxorubicin. Western blot was applied to assess the changes of MAPK pathway and protein expression of MRP1 and MRP3. Flow cytometry was used to measure intracellular doxorubicin accumulation after the treatment of MEK inhibitors. Results Both Raf1 inhibitor (GW5074) and MEK inhibitors (U0126 and AZD6244) suppressed HCC cell growth in a dose dependent manner. Pre-treatment of MEK inhibitor U0126 or AZD6244 sensitized HCC cells to gemcitabine or doxorubicin based chemotherapy. Raf1 inhibitor GW5074 had no effect on MRP1 and MRP3 protein expression. Treatment of gemcitabine or doxorubicin activated phosphorylated ERK and induced the upregulation of MRP1 and MRP3. MEK inhibitors U0126 and AZD6244 deactivated phosphorylated ERK, decreased endogenous MRP1 expression, reversed gemcitabine or doxorubicin induced MRP1 and MRP3 upregulation, and increased the intracellular doxorubicin accumulation. Conclusion This study provides evidence that MEK inhibitors sensitize HCC cells to chemotherapy by increasing intracellular chemodrug accumulation. MEK inhibirors U0126 and AZD6244 reduced MRP1 as well as MRP3 expression, and may contribute partially to the sensitization. The combination of MEK inhibitor and conventional chemotherapy may offer new therapeutic option for the treatment of resistant HCC.